Roxadustat (FG-4592) abated lipopolysaccharides-induced depressive-like symptoms via PI3K signaling - Li, Axiang; Liu, Zizhen; Ali, Tahir; Gao, Ruyan; Luo, Yanhua; Gong, Qichao; Zheng, Chenyou; Li, Weifen; Guo, Hongling; Liu, Xinshe; Li, Shupeng; Li, Tao (Frontiers in Molecular Neuroscience, 2023)
Background Despite its role in inflammation and the redox system under hypoxia, the effects and molecular mechanisms of hypoxia-inducible factor (HIF) in neuroinflammation-associated depression are poorly explored. Furthermore, Prolyl hydroxylase domain-containing proteins (PHDs) regulate HIF-1; however, whether and how PHDs regulate depressive-like behaviors under Lipopolysaccharides (LPS)-induced stress conditions remain covered. Methods To highlight the roles and underlying mechanisms of PHDs-HIF-1 in depression, we employed behavioral, pharmacological, and biochemical analyses using the LPS-induced depression model. Results Lipopolysaccharides treatment induced depressive-like behaviors, as we found, increased immobility and decreased sucrose preference in the mice. Concurrently, we examined increased cytokine levels, HIF-1 expression, mRNA levels of PHD1/PHD2, and neuroinflammation upon LPS administration, which Roxadustat reduced. Furthermore, the PI3K inhibitor wortmannin reversed Roxadustat-induced changes. Additionally, Roxadustat treatment attenuated LPS-induced synaptic impairment and improved spine numbers, ameliorated by wortmannin. Conclusion Lipopolysaccharides-dysregulates HIF-PHDs signaling may contribute to neuroinflammation-coincides depression via PI3K signaling.